What is the best noninvasive test of cure to confirm eradication ofH pyloriinfection?. Issue 11 (November 2017) - Sullivan, Anne L. S.; Watson, Joanne
Abstract : EVIDENCE‐BASED ANSWER : The urea breath test (UBT) and monoclonal stool antigen test (SAT) have similar sensitivities (95% and 91%) and specificities (100% and 97%) and similarly low negative likelihood ratios (LR‐ 0.05 for UBT and 0.09 for SAT) for confirming eradication of Helicobacter pylori . The sensitivity of UBT is decreased by use of proton‐pump inhibitors, and so should not be used in patients taking those medications. H pylori serology remains positive long after eradication and is not useful to confirm eradication (SOR: B, diagnostic cohort studies, cohort study, and longitudinal study).